(untitled) (REMUNOM, 2025)
Burnout syndrome is a recognized occupational phenomenon, particularly among nursing professionals, and has been widely associated with adverse consequences for workers’ health, the quality of care provided, and patient safety. This study aimed to determine the prevalence of burnout syndrome among nursing professionals in Brazil, identify the factors associated with its occurrence, and discuss the implications for healthcare services management. An integrative literature review was conducted, encompassing studies published between 2009 and 2018 in Portuguese, English, and Spanish. The literature search was performed in the LILACS, CINAHL, MEDLINE, Scopus, and Web of Science databases. Nineteen studies were analyzed, 18 cross-sectional and one longitudinal, with sample sizes ranging from 16 to 534 participants. The prevalence of burnout syndrome ranged from 0% to 84%, depending on the methodology employed. Age group, area of practice, work characteristics, and working two or more shifts emerged as associated factors. The findings underscore that burnout syndrome substantially undermines both professionals’ quality of life and the quality of patient care, constituting a public health concern that demands a more systematic and structured response. Professional recognition, extended work hours, and insufficient institutional support were identified as critical contributors to burnout. Recognizing and valuing nursing work, fostering a healthy work environment, reviewing workload and shift patterns, and implementing psychological support programs, as well as management policies focusing on continuous professional development, enhancing job satisfaction, and ensuring the participation of nursing staff in decision-making processes are strategies that may effectively mitigate the impacts of burnout and reduce its prevalence.